The Challenges of Anatomic Pathology Medical Education in Indonesia - Nora Ramkita; Krisna Murti (RSUP Dr Moh Hoesin Palembang, 2021)
The Covid-19 pandemic has changed many aspects of life in the world, including medical education. To create a public need for health service becomes one of basic philosophical specialist services in Indonesia. The existence of a specialist and the availability of infrastructure uneven in the Indonesia hospital have also been a burden to handle it together. The spread of 681 anatomic pathology doctors in 2019 have not spread evenly across Indonesia. That is because of infrastructure Anatomic Pathology at the hospital certain inadequate. The number is not as required minimum labour standards anatomical pathology doctors determined by the government. The right steps need to be taken to face these challenges so that we can create the good doctors, including a pathologist who is not only competent but also has good ethics and virtue.